2012
DOI: 10.1021/jp304310z
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Resonance Raman Spectroscopy and Docking Simulations to Study the Nonspecific Binding of a Free-Base Porphyrin to a Globular Protein

Abstract: Understanding the conformational changes induced by small ligands noncovalently bound to proteins is a central problem in biophysics. We focus on the binding location of the water-soluble porphyrin, meso-tetrakis (p-sulfonatophenyl) porphyrin, to a globular protein, β-lactoglobulin, which has been observed to partially unfold when irradiated by laser light. Identifying the binding location is necessary to determine the mechanism of action as well as the atoms and residues involved in the photoinduced partial u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…What was the initial biomedical investigation, has now morphed into a more basic biophysical approach to address the questions raised by the effects of laser irradiation on proteins. For instance, using a combination of Resonance Raman Spectroscopy (RRS), density functional theory (DFT) and docking simulations we have started to address the problem of establishing the location of the ligand [9]. We demonstrated that the approach is promising by establishing that certain porphyrins are able to prompt conformational changes in small globular proteins [7,8].…”
Section: Biophotonicsmentioning
confidence: 99%
“…What was the initial biomedical investigation, has now morphed into a more basic biophysical approach to address the questions raised by the effects of laser irradiation on proteins. For instance, using a combination of Resonance Raman Spectroscopy (RRS), density functional theory (DFT) and docking simulations we have started to address the problem of establishing the location of the ligand [9]. We demonstrated that the approach is promising by establishing that certain porphyrins are able to prompt conformational changes in small globular proteins [7,8].…”
Section: Biophotonicsmentioning
confidence: 99%
“…Following is a description of a recent methodology developed in our research group that uses a combination of experimental and computational techniques in order to obtain more detailed spatial information regarding the ligand/ protein complex. With this particular approach, one combines RRS with density functional theory (DFT) calculations and computational docking simulations (Parker, Thomas, Morisson, & Brancaleon, 2012).…”
Section: Combination Of Optical Spectroscopy and Computational Simulamentioning
confidence: 99%
“…This approach makes use of the 6-31G * basis set for the atoms in the molecule as long as the details of meso-or the beta-substituents are either ignored or replaced with a pseudo-atom that represents the characteristics of that substituents. For instance in one of our studies, the sulfonic acid groups (SO 3 À ) at the terminus of each phenyl in TSPP and replacing them with a hydrogen atom, that is, the simulation was reduced to a molecule of tetraphenylporphyrin (TPP) involving only hydrogen, carbon, and nitrogen atoms (Parker et al, 2012). Such simplification is justified by the fact that the laser wavelength (413 nm) primarily excites the porphyrin macrocycle; and therefore, the vibrational modes of the macrocycle will dominate the RR spectra which will minimize the effects of the groups appended to the phenyl meso-substituents.…”
Section: Density Functional Theorymentioning
confidence: 99%
See 2 more Smart Citations